PENGARUH PERSEPSI BAURAN PEMASARAN TERHADAP KEPUTUSAN MEMILIH PASIEN RAWAT INAP DI RUMAH SAKIT IBU ANAK LIMIJATI BANDUNG - Ratih Purnama Sari; Irda Sari (INFOKES (Informasi Kesehatan), 2021)
The purpose of this study, is to determine and analyze the effect of perceptions of the marketing mix, namely product, person, price, place, promotion, process, and physical evidence on the decision to choose inpatients at RSIA Limijati Bandung. This research method, namely explanatory through cross-sectional survey method, quantitative approach. The sample of this study, were patients in the maternal inpatient unit, the type of sampling was non-probability through a sampling technique. The sample consisted of 167 respondents. Hypothesis testing uses multiple linear regression analysis, namely the simultaneous test (f test) and partial test (t test), with the intention of knowing simultaneously and partially the effect of the independent and dependent variables at the 95% confidence level (α = 0.05) or 5% degree of error. The results of the research the effect of the perception of the marketing mix by simultaneous testing (f test), the decision H0 is rejected and Ha is accepted, meaning that simultaneously the marketing mix of the independent variable (X) has an effect on the decision of inpatients to choose RSIA Limijati Bandung. The results of the partial test (t test), for product mix, people, and physical evidence showed an effect, while the mix of prices, place, promotion and process, showed no effect on the decision to choose RSIA Limijati Bandung. The value of the coefficient of determination or R2, which is influenced by 62.6%, while the remaining 37.6% is the contribution of other independent variables not included in this study.